KCC-1-NH2-DPA: an efficient heterogeneous recyclable nanocomposite for the catalytic synthesis of tetrahydrodipyrazolopyridines as a well-known organic scaffold in various bioactive derivatives - Sajjad Azizi (Taylor & Francis Group, 2019)
In this study, a novel approach has been used for the efficient synthesis of tetrahydrodipyrazolopyridine derivatives (5a–m) via a four-component one-pot condensation reaction of aromatic aldehydes, hydrazinehydrate, ethyl acetoacetate, and ammonium acetate in the presence of KCC-1-npr-NH2-DPA as an advanced nano-catalyst in ethanol under reflux conditions at 30 min. For this purpose, mesoporous fibrous nano-silica functionalized by dipenicillamine as a novel nanocatalyst (KCC-1-npr-NH2-DPA) was synthesized using a hydrothermal protocol. KCC-1-npr-NH2-DPA nano-catalyst is easily recyclable eight times without the considerable loss of catalytic activity. Other remarkable features include the short reaction time, simple work-up procedure and providing excellent yields (89–98%) of the products under mild reaction conditions. Furthermore, the effects of solvent, concentration of catalyst, time and temperature for the synthesis of tetrahydrodipyrazolopyridine (5a) were studied.